Professional SharePoint 2013 development - Alirezaei, Reza; Schwartz, Brendon (Wrox, 2013)
Thorough coverage of development in SharePoint 2013 A team of well-known Microsoft MVPs joins forces in this fully updated resource, providing you with in-depth coverage of development tools in the latest iteration of the immensely popular SharePoint. From building solutions to building custom workflow and content management applications, this book shares field-tested best practices on all aspect of SharePoint 2013 development. Offers a thorough look at Windows Azure and SharePoint 2013 Includes new chapters on Application Life Cycle Management, developing apps in SharePoint, and building PerformancePoint Dashboards in SharePoint Professional SharePoint 2013 Development is an essential SharePoint developer title.